Bookmarking promoters in mitotic chromatin: poly(ADP-ribose)polymerase-1 as an epigenetic mark - Lodhi, Niraj (Oxford University Press, 2014)
Epigenetics are the heritable changes in gene expression or cellular phenotype caused by mechanisms other than changes in the underlying DNA sequence. After mitosis, it is thought that bookmarking transcription factors remain at promoters, regulating which genes become active and which remain silent. Herein, we demonstrate that poly(ADP-ribose)polymerase-1 (PARP-1) is a genome-wide epigenetic memory mark in mitotic chromatin, and we further show that the presence of PARP-1 is absolutely crucial for reactivation of transcription after mitosis. Based on these findings, a novel molecular model of epigenetic memory transmission through the cell cycle is proposed.